Effect of Skim Nanoparticles on the Motility and Kinematics of Simmental Cattle Frozen Semen - Anggraeni, Fitri Dian; Rasad, Siti Darodjah; Solihati, Nurcholidah (Faculty of Agriculture, 2024)
Nanotechnology has positively impacted the development of extenders used in the cryopreservation of spermatozoa in livestock. The inclusion of nano skim in the extender is expected to preserve semen quality after thawing. This study aimed to determine the optimal concentration of nano skim. Various concentrations of nano skim (0%, 1.66%, 3.33%, 5%, 6.66%, 8.33%, and 10%) with the addition of 10% nano egg yolk in each extender were compared. Fresh semen samples were collected from three three-year-old Simmental bulls using an artificial vagina. The study parameters included motility (total motility, progressive motility) and kinematics (velocity curve linear (VCL), velocity straight linear (VSL), velocity average pathway (VAP), amplitude lateral head (ALH), beat cross frequency (BCF), straightness (STR), linearity (LIN), and wobble (WOB). A completely randomized design was employed, and data were analyzed using analysis of variance (ANOVA). Fresh semen dilution results indicated that only the control group (0%) and the nano skim group with concentrations of 6.66% and 8.33% were eligible for further processing into frozen semen. The results showed no significant difference between the three treatment groups on sperm motility and kinematics of Simmental cattle after thawing (p0.05). The control group exhibited the highest percentage of total motility, VCL, VAP, and ALH values, while the 6.66% nano skim group outperformed the 8.33% nano skim group. The highest percentage of progressive motility and VSL value was observed in the 6.66% nano-skim group compared to the 8.33% nano-skim and control groups. The highest values of BCF, WOB, LIN, and STR was observed in the nano-skim group at 8.33% compared to the nano-skim group at 6.66% and control. The study concluded that 6.66% nano skim was the optimal concentration to maintain the quality of frozen semen of Simmental cattle.